Algoritmizace pro podporu rozhodování - Šišlák, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Bakalářská práce je zaměřena na vývoj cenových indikátorů, které se využívají k efektivnímu obchodování na burze. Součástí práce je technická analýza vybraného měnového páru v daném čase a na základě výsledků vytvoření efektivního indikátorů a testování v různých časových intervalech.

The bachelor thesis is focused on the development of price indicators, which are used for effective trading on the stock exchange. Part of the work is a technical analysis of the selected currency pair at a chosen time and based on the results of create effective indicators and test them at different time intervals.
Algorithmization for decision support
Keywords: obchodování; programování; burza; kryptoměny; cenový graf; backtestování; optimalizace; trading; programing; stock exchange; cryptocurrencies; price chart; backtesting; optimalization